Marine, Benthic algae from Southernmost Greenland. - Pedersen, Poul Møller (Meddelelser om Grønland, 1976)
One hundred and twenty-four species of marine algae from South Greenland are dealt with, of which 11 belong in the Cyanophyceae, 28 in the Rhodophyceae, and 1 each in the Chrysophyceae, Dinophyceae, and Xanthophyceae, respectively, 49 in the Phaeophyceae and 33 in the Chlorophyceae. Of the 11 Cyanophyceae 4 have not previously been reported from Greenland: Aphanothece sp., Nostoc minutum, Hydrocoleum lyngbyaceum and Lyngbya infixa. Further, new observations are presented concerning cell divisions, which resulted in daughter cells of uneven size, in Pleurocapsa amethystea, and two new host plants, Rhodochorton purpureum and Ulothrix speciosa, are reported for Sarcinastrum urosporae in Greenland. All the red algae are well known from literature, but additional information are given especially with regard to reproductive structures. Antheridia-like cells were observed in Rhodochorton spetsbergense and in Audouinella membranacea in plants that also bore tetrasporangia. The present data support the combining of Rhodochorton penicilliforme with Rhodochorton spetsbergense. For Rhodophysema elegans some details concerning the formation of tetrasporangia and the presence of branched paraphyses are reported. Female gametophytes as well as a presumed male gametophyte of Antithamnion boreale have been found for the first time in nature in Greenland. It is suggested that this species has a typical Polysiphonia-type of life history in this part of its distribution. This suggestion is supported also from observations from cultures recently established. Callocolax neglectus, presently known as a red algal parasite on Callophyllis laciniata, was found and further described growing on Callophyllis cristata, which is a new host for this parasite. The known distribution for Greenland of H alosacciocolax kjellmanii, previously known from the type locality in Scoresby Sund only, has been considerably extended. The brown algae Myriactula clandestina and Streblonema chordariae are reported from Greenland for the first time, the latter from an old collection by ROSENVINGE. A new find of Phaeostroma parasiticum is reported and the relation to P. pustulosum is discussed. Additional information are given on Porterinema flufliatile, including a new host plant, Delamarea attenuata. In some cases supplementary information have been added from culture studies of algae from the Godthåbsfjord, West Greenland. Thus the development of hairs in Phaeostroma pustulosum has been followed, and the taxonomic reliability of this character confirmed. The presence of a microthallus and hair-like structures in the life his tory of Elachista fueicola has been demonstrated, and it is suggested to give up the combination Myriactula lubrica. The culture studies also support the assumption that Pilayella littoralis and P. paria are conspecific, and suggest a removal of Litosiphon filiformis from the genus Litosiphon. All the green algae found are well known to science. It is suggested to remove Entoderma wittrockii from the flora of Greenland. Culture studies indicate that Chlorochytrium inclusum is connected with Acrosiphonia (possibly A. sonderi) in Greenland, while Chlorochytrium cohnii is an independant species.